The Effect Of Raw Material Costs And Promotional Costs On Sales Volume - Siti JAENAB; Yuldi MILE; Jurana JURANA; Jamaluddin JAMALUDDIN; Mustamin MUSTAMIN (Journal of Tourism Economics and Policy, 2021)
This article describes how the cost of raw materials and promotional costs affect the sales volume generated by the company. This research aims to find out that the cost of raw materials and promotion costs can increase sales volume. This study uses secondary data, obtained from the annual reports of each company with the years published 2018, 2019 and 2020. The number of observations is 105 data determined by the purposive sampling method. Multiple linear regression is an analytical tool in this study. The results showed that the cost of raw materials partially affects sales volume, the promotion also costs partially affect sales volume. Simultaneously the cost of raw materials and promotion costs affect sales volume. The raw material costs incurred by the company are used to produce products that follow market demand both in terms of quality and quantity, and the company can use promotional costs appropriately.